Incidence of cervical stump metastasis after subtotal hysterectomy done to cases proved later by histopathology to be endometrial cancer in Al Shatby university maternity hospital patients - El Sokkary, Hossam; Abd El Zaher, Eman (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Subtotal hysterectomy is associated with lesser complication, lesser time consuming than total one, but total hysterectomy has advantage of radicality of its management in cases of accidentally undiagnosed endometrial cancer proved later on by histopathology, that why hysterectomy should be total even in apparently benign causes that indicate it. The aim of this study was to access incidence of cervical stump invasion by malignancy in endometrial cancer cases and its relation to pathological types after subtotal hysterectomy done to cases proved later by histopathology to be endometrial cancer. Methods: Following approval by our institutional ethics committee a prospective and retrospective observational descriptive study was done on 100 patients recruited from gyne-oncological outpatient clinic of Shatby university hospital of Alexandria from August 2018 to June 2021 with past history of subtotal hysterectomy. All these cases were proved later after histopathological examination of the uterine body to have type 1 or type 2 endometrial cancer. Stumpectomy was done to all patients after a written informed consent were taken from them before the study. Histopathological examinations of the cervical stumps were done and incidence of stump invasion with cancer in relation to its type was analyzed. Results: Histopathological examination of the stump of all cases revealed that only 13 cases showed microscopic stump invasion. 7 cases with stump invasion were type 1 endometrial cancer, 4 cases were grade 1 and 3 cases were grade 2 in relation to 6 cases of stump invasion were type 2 endometrial cancer with papillary serous adenocarcinoma. Regarding relation between stump invasion and pathological types of endometrial cancer there was a significant statistical difference between them as type 2 are associated by higher number of stump invasion (p=0.0001). Conclusions: The present study concluded that cases subjected to subtotal hysterectomy with undiagnosed endometrial cancer are associated with considerable incidence of cervical stump invasion and type 2 endometrial cancer have higher incidence of cervical stump invasion in relation to type 1 endometrial cancer.